STRATEGI KOPING DALAM KESIAPAN MENGHADAPI PERSALINAN PADA IBU HAMIL PREEKLAMPSIA - Alis Nurdiana (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
ABSTRACT Each mother needs the readiness of laborespecially in preeclampsia pregnant women.Based on preliminary study indicated manyunreadiness of mother in facing childbirth inpreeclampsia pregnant mother in obstetric andgynecologic poly that is influenced by severalfactors such as age, education, parity, work,etc. The purpose of this research is to analyzethe relationship between coping strategies andthe readiness to face labor in preeclampsiapregnant women.This study is a kind of analytic research withcross sectional design. Population in this studyis 45 in preeclampsia pregnant women and 40respondents as sample by using simple randomsampling tehnique. Independent variable iscoping strategy and dependent variable is readiness to face labor in preeclampsiapregnant mother.The results of this study indicated mostrespondents had less coping strategy (55%)and most pregnant women who hadpreeclampsia unreadiness (77,55). Based onthe results of spearman rank test statisticalanalysis significant value of 2-tailed 0,001 soH0 rejected and H1 accepted therefore there isa relationship between coping strategies withthe readiness to face labor in preeclampsiapregnant women Midwives are expected to be able to provideintegrated ANC care in service, one of which iscounseling about the readiness of mothers inthe face of childbirth